2018
DOI: 10.1021/acssuschemeng.8b04173
|View full text |Cite
|
Sign up to set email alerts
|

Climbing the 3D Volcano for the Oxygen Reduction Reaction Using Porphyrin Motifs

Abstract: A major contribution to the energy loss in fuel cells originates from poor kinetics of the oxygen reduction reaction (ORR) at the cathode. The ORR mechanism has been understood in descriptor-based approaches, which reveal an activity volcano with a significant overpotential of at least 0.4 V. This energy loss is directly linked to the scaling relation between the binding energy of the ORR intermediates, OH and the OOH. It has become apparent that new catalyst designs are necessary in order to circumvent this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 48 publications
1
54
0
Order By: Relevance
“…Linear scaling correlations among the ORR intermediates on the structurally stable metal-heteroatom-doped carbon structures were observed for ΔG OOH or ΔG O vs. ΔG OH . The slope and intercept for the correlation between OH and OOH were 0.92 and 3.07, respectively, with a correlation coefficient ( R 2 ) value of 0.97, which is consistent with previous research ( Calle-Vallejo et al, 2017 ; Kulkarni et al, 2018 ; Wan et al, 2019 ) ( Figure 3B ). Meanwhile, the scaling relationship between OH and O+OH was highly linear with a slope value of 1.24, an intercept value of 0.37, and an R 2 value of 0.79.…”
Section: Resultssupporting
confidence: 91%
“…Linear scaling correlations among the ORR intermediates on the structurally stable metal-heteroatom-doped carbon structures were observed for ΔG OOH or ΔG O vs. ΔG OH . The slope and intercept for the correlation between OH and OOH were 0.92 and 3.07, respectively, with a correlation coefficient ( R 2 ) value of 0.97, which is consistent with previous research ( Calle-Vallejo et al, 2017 ; Kulkarni et al, 2018 ; Wan et al, 2019 ) ( Figure 3B ). Meanwhile, the scaling relationship between OH and O+OH was highly linear with a slope value of 1.24, an intercept value of 0.37, and an R 2 value of 0.79.…”
Section: Resultssupporting
confidence: 91%
“…It can be seen that several aspects are unclear: the electronic character of the N-donors, the presence and nature of axial ligands, the type and abundance of defects close to the active site, and the position of the active site within a sheet, at the edge, or positioned between two sheets. [39,44,[53][54][55][56][57][58] While other spectroscopies fall short because of the amorphous nature of the SAC material, Mössbauer spectroscopy is ideally equipped to study the coordination environments and electronic structures of iron sites within the amorphous material. However, the definitive assignment of structural characteristics proves difficult purely by comparison with reference data from model complexes.…”
Section: Introductionmentioning
confidence: 99%
“…11,13 A promising strategy towards this goal is the confinement of *OOH within a 3-D active site environment, which has been demonstrated for a few model systems and homogenous molecular catalysts. For instance, Rossmeisl et al 14,15 have shown that diporphyrin motifs are capable of facilitating *OOH dissociation via two closely-spaced binding sites. This approach bypasses the limitations imposed by *OOH scaling in favor of the less restrictive dissociated *O + *OH pathway.…”
mentioning
confidence: 99%